Experiences in coverage testing of a Java middleware. - Kessis, Mehdi (Software engineering notes.)
This paper addresses the issues of test coverage analysis of J2EE [22] servers. These middleware are nowadays at the core of the modern information technology's landscape. They provide enterprise applications with several non functional services such as security, persistence, transaction, messaging, etc. In several cases, J2EE servers play a critical role when applied to e-business or banking applications. Therefore, ensuring the quality of such software layers becomes an essential requirement. However, in industrial context, professional middleware software are highly complicated and have a huge size which makes their maintenance and quality management a big challenge for testers and quality managers. The aim of this paper is to present our test and coverage analysis case study with and the JOnAS [23] J2EE server. The challenges of this work result from the size of the test suites and the size of the tested middleware (200,000 lines of code (LOC) for JOnAS)